1992
DOI: 10.1093/eurheartj/13.suppl_e.85
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of myocardial oxygen consumption (Vo2) and systolic pressure-volume area (PVA) in human hearts

Abstract: Several studies have recently reported that the relationship between myocardial oxygen consumption per beat (Vo2) and left ventricular (LV) systolic pressure-volume area (PVA), which represents total mechanical energy generated by contraction, is linear and independent of loading conditions in excised, supported, and intact hearts. We assessed the Vo2-PVA relationship in nine patients with heart disease. LV volume and pressure were measured simultaneously by conductance catheter and tip-micromanometer. Vo2 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0
3

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 0 publications
3
55
0
3
Order By: Relevance
“…Furthermore, previous studies have shown that reduced LV wall stress and stroke work correlate with reduced myocardial oxygen consumption. 38,39 Our data suggest that reducing LV wall stress, stroke work, and strain may promote myocardial salvage in AMI by reducing myocardial oxygen demand and thereby attenuating the process of ongoing myocardial ischemia.By initiating mechanical support first and sustaining systemic perfusion while reducing native LV work, we have created a window in time when the process of myocardial injury is slowed and delaying coronary reperfusion is possible while incurring only minimal additional ischemic damage. By delaying reperfusion in the setting of mechanically reduced oxygen demand, time is now available for activation of signaling pathways known to promote myocardial salvage, including phosphorylation of ERK and Akt.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, previous studies have shown that reduced LV wall stress and stroke work correlate with reduced myocardial oxygen consumption. 38,39 Our data suggest that reducing LV wall stress, stroke work, and strain may promote myocardial salvage in AMI by reducing myocardial oxygen demand and thereby attenuating the process of ongoing myocardial ischemia.By initiating mechanical support first and sustaining systemic perfusion while reducing native LV work, we have created a window in time when the process of myocardial injury is slowed and delaying coronary reperfusion is possible while incurring only minimal additional ischemic damage. By delaying reperfusion in the setting of mechanically reduced oxygen demand, time is now available for activation of signaling pathways known to promote myocardial salvage, including phosphorylation of ERK and Akt.…”
mentioning
confidence: 83%
“…Furthermore, previous studies have shown that reduced LV wall stress and stroke work correlate with reduced myocardial oxygen consumption. 38,39 Our data suggest that reducing LV wall stress, stroke work, and strain may promote myocardial salvage in AMI by reducing myocardial oxygen demand and thereby attenuating the process of ongoing myocardial ischemia.…”
mentioning
confidence: 83%
“…Based on their diagram (Suga and Sagawa, 1974), they described the ratio of instantaneous pressure to instantaneous volume (P(t)/(V(t) − V d )) as the time varying stiffness of ventricular chamber. The standard P-V diagrams are easy to interpret and give a rough estimate of the mechanical work done by the LV (Takaoka et al, 1992). However, the pressure and the corresponding volume of the LV need to be measured invasively using sophisticated techniques, such as intravascular micromanometers and conductance catheters (Applegate et al, 1990), which restrict the clinical applications of this model.…”
Section: Introductionmentioning
confidence: 99%
“…Suga et al (1979Suga et al ( , 1983 and Takaoka (1992) have made similar estimates based on the PVA method, and ventricular free wall movement. Regardless, better models of the coronary circulation and gas transport in the myocardium are needed to make better estimates of energy consumption based the A-VO 2 difference across the coronary capillary bed.…”
Section: Model Limitationsmentioning
confidence: 89%
“…Currently, the rate of energy consumption per heartbeat is taken to be the area enclosed by the P-V loop (Westerhoff 2000;Suga 1979a;1981;Takaoka et al 1992); however, most analyses using this method do not include the effects of the interventricular septum. The current lack of adequate amounts of measured patient data has slowed the development of functional models capable of analyzing septal and free ventricular wall mechanics.…”
Section: Introductionmentioning
confidence: 99%